Legal Study of Employment Agreements Made by Companies with Workers in View of Legislation (Study at PT. Bina Artha Sei Rampah) - Randu, Zaura; Abduh, Rachmad (Inspiring Law Journal, 2024)
The holding of a work agreement is an implementation of statutory regulations. By making a work agreement, it is intended as a reference in regulating industrial relations between employees and PT Bina Artha Ventura (Bina Artha) is a Venture Capital Company that is growing rapidly and has been actively involved in the microfinance sector in Indonesia since December 2011. So that the mission of PT Bina Artha, namely, provides easy and innovative access for Indonesian families. PT Bina Artha was able to form and develop thanks to the contribution of employees who work with high ethical standards and work enthusiasm and in accordance with the partner segments served by PT Bina Artha. The research method used in this thesis is an empirical juridical type with a statutory approach and is descriptive. Data sources involve revealed and primary data, collected through interviews, data collection, and documentation or literature studies. The analysis used is qualitative analysis. The aim of this research is to understand the form of work agreement at PT Bina Artha, assess the implementation of work agreements based on statutory regulations, and identify factors inhibiting work agreements at PT Bina Artha Sei Rampah. The results of this research are that the form of employment agreement at PT Bina Artha according to law is written. workers at PT. Bina Artha is part of the scope of work agreements in statutory regulations. PT Bina Artha's work agreement only carries out a written work agreement for an indefinite period of time (PKWTT). Implementation of work agreements at PT. Bina Artha viewed from the statutory regulations Law Number 13 of 2003 concerning Employment and Law Number 6 of 2023 concerning Job Copyright, the work agreement that has been agreed between the company and employees is a company regulation which contains all work rules, hours. work, wages, and the rights and obligations of workers or companies. This is in accordance with the principles in the Law. The inhibiting factor for employment agreements at PT Bina Artha is that the Holiday Allowance (THR) received by workers from the company does not comply with the contents of the employment agreement